Is Uganda Ready for Oil Revenues? - Tumusiime, Francis (The Governance of Africa’s Resources Programme, 2011)
Following the discovery of substantial petroleum deposits in Uganda, expectations are high that oil revenues will lead to economic prosperity and improved standards of living. However, if not handled properly, oil revenues can exacerbate the resource curse. Overcoming the resource curse requires laws and institutions that foster transparency and accountability. Most of the required institutions provided for in the Oil and Gas Policy of 2008 are not yet in place, and whether the proposed institutions will function effectively and independently is not clear. Despite revenue transparency being touted as a key policy objective, to date no bill for the management of oil revenues is in place, and the law does not guarantee access to information for effective participation. Moreover, as oil extraction is new to Uganda, insufficient capacity exists among key stakeholders generally. It is hoped the recommendations made in this briefing will go some way in improving the current state of affairs.